(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2026)
The paper analyzes the functioning of passenger transport in municipalities of resort areas.The recommendations developed in this article are mainly based on the fact that most public transport facilities have been privatized in the Zomin health center, a large number of individual carriers and small private enterprises have appeared, which are engaged in the organization of passenger transport, and in this regard, the need to consider the passenger transport management system in the area, taking into account its uniqueness and characteristics. In this case, the formation of the main goals and tasks that arise will serve to increase the activity in providing the demand.